Biologic effects of nanoparticle-allergen conjugates: time-resolved uptake using an in vitro lung epithelial co-culture model of A549 and THP-1 cells. Issue 9 (9th August 2018) - Grotz, Bettina; Geppert, Mark; Mills-Goodlet, Robert; Hofer, Sabine; Hofstätter, Norbert; Asam, Claudia; Feinle, Andrea; Kocsis, Krisztina; Berger, Thomas; Diwald, Oliver; Hüsing, Nicola; Wallner, Michael; et al.
Abstract : Nanotechnology is a fast growing field and already a multi-billion dollar market with numerous consumer products. Abstract : Nanotechnology is a fast growing field and already a multi-billion dollar market with numerous products available for consumers. TiO2 and SiO2 are by mass the most produced nanomaterials and, thus, of particular interest regarding their biological effects upon inhalation – especially in combination with other inhalable biomolecules such as allergens. We investigated the protein-binding capacity of these two nanomaterials and present detailed uptake profiles of protein-conjugated TiO2 or SiO2 nanoparticles (NPs) in A549 lung epithelial and THP-1 macrophage-like cells. TiO2 and SiO2 NPs (both with a hydrodynamic diameter of about 150 nm) are able to bind bovine serum albumin (BSA), green fluorescent protein (GFP) and the major birch pollen allergen Bet v 1 in substantial amounts that suggest protein monolayers around the particles. GFP-conjugated TiO2 and SiO2 NPs were taken up in A549 and THP-1 cells in a time-dependent manner as demonstrated by confocal laser scanning microscopy, flow cytometry and life cell imaging. By the aid of fluorescent proteins (GFP or fluorescently labeled Bet v 1) we found that both, the NPs and the conjugated proteins entered the cells. Using A549/THP-1 co-cultures, we showed that the majority of SiO2 NPs is taken up by THP-1 cells; however, also A549 cells take up significant amounts of particles when co-cultured with THP-1 macrophage-like cells. The here discussed data provide valuable insights into protein (allergen) delivery by NPs at the lung epithelial barrier.